Ubuntulisation of mathematics classroom for the enhancement of learner’s interest and achievement - Terungwa James Age (CV. FOUNDAE, 2024)
Background: One of the primary challenges confronting African mathematics educators and students is the wholesale adoption of external methods, approaches, and ideas in the teaching and learning of mathematics. In response to this challenge, the concept of ethnomathematics has emerged, although it remains largely unadopted across many African countries. Recently, Social Justice Mathematics has been developed, a concept closely aligned with the principles of Ubuntu, which emphasizes equality and justice in all aspects of human life. Aim: This paper aims to highlight the ubuntulisation of mathematics classrooms. Instead of fully adopting Social Justice Mathematics as a contemporary solution to enhance students' interest and achievement in mathematics, this paper proposes an Africanized approach by integrating Ubuntu as a foundational element of ethnomathematics. This approach is posited to achieve greater success among learners. Methods: The study involves a comprehensive review of existing literature on ethnomathematics, Social Justice Mathematics, the benefits of Social Justice Mathematics in learning, Ubuntu pedagogy, and the ubuntulisation of mathematics classrooms.Results: The paper presents relevant examples that emphasize the need for mathematics educators to incorporate African cultural contexts in the planning and teaching of mathematics.Conclusion: The study concludes by recommending the ubuntulisation of mathematics classrooms as an effective alternative to Social Justice Mathematics for enhancing students' interest and achievement in mathematics.